2019
DOI: 10.1080/23802359.2019.1661301
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Leucobryum juniperoideum (brid.) C. Müll. (Leucobryaceae, Bryophyta)

Abstract: The complete chloroplast genome of Leucobryum juniperoideum (brid.) C. M€ ull.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“… 2020 ), L. juniperoideum (MK952779, Min et al. 2019 ), L. incana (NC_042174), M. maximowiczii (MT726030, Han et al. 2020b ), O. rogeri (NC_026212), P. patens (NC_005087), P. inflexum (MK131349), P. nutans (NC_045869, Jin et al.…”
Section: Resultsmentioning
confidence: 99%
“… 2020 ), L. juniperoideum (MK952779, Min et al. 2019 ), L. incana (NC_042174), M. maximowiczii (MT726030, Han et al. 2020b ), O. rogeri (NC_026212), P. patens (NC_005087), P. inflexum (MK131349), P. nutans (NC_045869, Jin et al.…”
Section: Resultsmentioning
confidence: 99%
“…NGS raw reads of truffle (SRA accession: SRR5005499) were downloaded from NCBI and processed under the Genome Information System (GeIS, http://geis.infoboss.co.kr) which has been utilized in various genomics studies. 79,13,14,17,19,20,2583 SRR5005499 dataset used in this study contains 29,010,538 100-bp-reads (2,901,053,800 bp). In the pipeline, de novo assembly and confirmation were done by Velvet v1.2.10…”
Section: Methodsmentioning
confidence: 99%
“…NGS raw reads of truffle (SRA accession: SRR5005499) were downloaded from NCBI and processed under the Genome Information System (GeIS, http://geis.infoboss.co.kr ) which has been utilized in various genomics studies. 7 9 , 13 , 14 , 17 , 19 , 20 , 25 …”
Section: Methodsmentioning
confidence: 99%
“…After getting first draft of chloroplast genome sequences, gap was filled with GapCloser v1.12 (Zhao et al, 2011) and all bases from the assembled sequences were confirmed using BWA v0.7.17 (Li, 2013) and SAMtools v1.9 (Li et al, 2009). All bioinformatic processes for de novo assembly was conducted by the pipeline, Genome Information System (GeIS; http://geis.infoboss.co.kr), which has been efficiently utilized and optimized in the previous studies (Min et al, 2019;Yun et al, 2019;Kim et al, 2021aKim et al, , 2021bPark et al, 2021b).…”
Section: De Novo Assembly and Annotation Of Diarthron Linifolium Chloroplast Genomementioning
confidence: 99%